2004
DOI: 10.1073/pnas.0402354101
|View full text |Cite
|
Sign up to set email alerts
|

Bardet–Biedl syndrome type 4 (BBS4)-null mice implicate Bbs4 in flagella formation but not global cilia assembly

Abstract: The functions of the proteins encoded by the Bardet-Biedl syndrome (BBS) genes are unknown. Mutations in these genes lead to the pleiotropic human disorder BBS, which is characterized by obesity, retinopathy, polydactyly, renal and cardiac malformations, learning disabilities, and hypogenitalism. Secondary features include diabetes mellitus and hypertension. Recently, it has been suggested that the BBS phenotypes are the result of a lack of cilia formation or function. In this study, we show that mice lacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
305
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 310 publications
(334 citation statements)
references
References 17 publications
25
305
2
2
Order By: Relevance
“…Second, there are three relevant knockout mouse models for genes within the linked interval: Pappa (31), Astn1 (paralogue of Astn2) (32), and Tlr4 (33). These models do not have phenotypes that resemble BBS mouse models (34)(35)(36). Finally, functional characterization of other TRIM proteins indicates involvement with components of the cytoskeleton, a finding consistent with the function of other BBS proteins (37)(38)(39).…”
Section: Discussionsupporting
confidence: 56%
“…Second, there are three relevant knockout mouse models for genes within the linked interval: Pappa (31), Astn1 (paralogue of Astn2) (32), and Tlr4 (33). These models do not have phenotypes that resemble BBS mouse models (34)(35)(36). Finally, functional characterization of other TRIM proteins indicates involvement with components of the cytoskeleton, a finding consistent with the function of other BBS proteins (37)(38)(39).…”
Section: Discussionsupporting
confidence: 56%
“…Since obesity and several of the other phenotypes that accompany BBS are common, studying this disorder potentially will yield new insights into the cellular and molecular mechanisms that underlie these important phenotypes. That several of the disease phenotypes (retinal dystrophy, situs inversus, and anosmia) already were linked to cilia suggested a connection between BBS and cilia, and several recent studies have confirmed this idea [94][95][96][97] (reviewed in Mykytyn and Sheffield 98 ). The BBS1 and BBS4 gene products are essential for formation of normal cilia in mouse olfactory epithelium.…”
Section: Cilia and The Obesity Disorder Bardet-biedl Syndromementioning
confidence: 65%
“…97 Interestingly, BBS4 knockout mice also undergo apoptotic retinal degeneration and males are sterile because their sperm fail to form a flagellum. 95,96 On the other hand, the BBS4 mice (which exhibit anosmia) show normal motile cilia in the airway and respiratory epithelial, as well as cilia of normal appearance in the renal epithelium. Thus, BBS4 protein is not globally required for cilia formation.…”
Section: Cilia and The Obesity Disorder Bardet-biedl Syndromementioning
confidence: 99%
“…At birth, Bardet-Biedl-Syndrome 4 (Bbs4) mutant mice are runted compared with their wild-type littermates and manifest obesity later on 15 . Penetrance is dependent on sex and age of the animals both in this and another Bbs4 À / À mutant strain 16 . Generally, female mutants are more severely affected than age-matched male mutants.…”
Section: Resultsmentioning
confidence: 99%